2021
DOI: 10.47631/jsrmbs.v2i2.248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Density on the Performance Characteristics, Egg Quality, and Nutrient Composition of the Eggs of Japanese Quails (Coturnix Coturnix Japonica)

Abstract: Purpose: The aim is to study the effects of stocking density on the performance characteristics, egg quality, and nutrient composition of the eggs of Japanese quails (Coturnix coturnix japonica). Study Design: Completely Randomized Design (CRD). Subjects and Methods: Two hundred and ninety-six (296) day-old sexed Japanese quails assigned to four different stocking densities (treatments) with four replicates conducted in the rainy season. The groups (I to IV) contained 11, 16, 21, and 26 quails in the approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
4
2
1
Order By: Relevance
“…were in agreement with the results of (Al-Hamed, 2020), (Al-Hamed, 2021), (Aro et al, 2021) and (Al-Tammee, 2019).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…were in agreement with the results of (Al-Hamed, 2020), (Al-Hamed, 2021), (Aro et al, 2021) and (Al-Tammee, 2019).…”
Section: Resultssupporting
confidence: 91%
“…The weight of birds in the seventh week was (275.57, 274.94 and 251.53) grams respectively and this could be due to the increase in the amount of feed consumed by the birds for the same two treatments, as shown in Table 3, because of the competitive behavior of the quail birds. These results were in agreement with the results of (Al-Tammee, 2019; Bolacali and Irak, 2017) and in disagreement with the results of (Cengiz et al, 2015) and Aro et al (2021) found that density of breeding had no significant effect on the body weight.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Recently, Bourdon et al (2021) evaluated the effects of four SD for laying Japanese quails and found that different SD did not affect performance and eggshell quality of laying quails, and suggested that the best SD is 102 cm 2 /quail. Also, Aro et al (2021) evaluated the effects of four stocking densities on the performance and egg quality of Japanese quails and stated that Japanese quails kept at 173.43 or 132.10 cm 2 /bird performed well as did those kept at the standard SD (252.20 cm2/quail bird) and hence could still be adopted in quail farming without compromising their welfare and performance. More recently El Sabry et al (2022) stated that taking the economicswelfare balance into account the optimal range of SD for laying quails is 200-230 cm 2 /bird.…”
Section: Introductionmentioning
confidence: 99%